(3YeOI GdEUdGM aj Yed UfGYI GdLQGMs - (3jYbhH Hf ESMGb GdeSjMji Gdedcj GdcQcj GHf Gdba, CHh GdaQL,J (B685 (3g` s
(3ChdgG (B:s
(3hHYO (B: (3abO TcG Edi HYV LQGMi ReGffG gPG bdI GgJeGe CQHGH gPG Gdaf HCeQ gPg GdUfGYI s
(3BNQgG (B:s
(3QWdjf , jOb hjVGa Edjg ChdkG aChdG , hjLYd ai TeS MGQI KdGKjf jhe , hjMQc cd jhe s
(3QJHg Ydi YTQjf ebGdIs
(3efbhdI ef fSNI bhHdJ Ydi eShOI GdeDda (B680(3g`s
(3hfbd GdfGSN HBNQgG JQLeI GHf Gdba ef cJH GdWHbGJs
(3hef GdeNJGQ ef WHbGJ GdCWHGA s
(3dGHf ReQ GdCQHdi s
(3bQf GdfSN (B:s
Keywords: (3GdWHs